2004
DOI: 10.1007/s00520-003-0532-y
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of head and neck cancer

Abstract: The findings presented contribute to quality of life (QOL) research by highlighting the significance of factors affecting the communication by patients with primary-stage squamous cell carcinoma of the head and neck cancer (SCCHN) of their experiences of suffering after treatment to their clinicians. Qualitative research methodology based on open-ended interviews with 18 survivors of American Joint Committee on Cancer primary stage I and II SCCHN were used. The interviews were transcribed verbatim and thematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…-81 year old, female, breast cancer survivor cancer survivors and patients receiving cancer treatment have reported similar feelings of perceived injustice and painrelated distress resulting in a lost sense of identity, reduced quality of life, and persistent worry about the future, even after becoming disease free. 10,18,30,31 Similar to another study, 8 participants in our study reported sometimes feeling dismissed by providers when presenting with pain. They described inadequate pain assessment and some participants described minimizing their own pain for fear of being dismissed or seen as complaining to providers who may have saved their lives.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…-81 year old, female, breast cancer survivor cancer survivors and patients receiving cancer treatment have reported similar feelings of perceived injustice and painrelated distress resulting in a lost sense of identity, reduced quality of life, and persistent worry about the future, even after becoming disease free. 10,18,30,31 Similar to another study, 8 participants in our study reported sometimes feeling dismissed by providers when presenting with pain. They described inadequate pain assessment and some participants described minimizing their own pain for fear of being dismissed or seen as complaining to providers who may have saved their lives.…”
Section: Discussionsupporting
confidence: 87%
“…One prior qualitative study reported a similar finding, where patients on active cancer treatment feared being fully forthcoming with their providers about their pain, potentially leading to incomplete pain management. 10 Since providers may not know that their patients have persistent or significant pain after cancer treatment, they may not prioritize its assessment during survivorship encounters. Some participants in our study described the use of the 0-10 pain score as a vital sign to assess pain but felt it did not fully capture the multidimensional aspects of their chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least 90% are diagnosed as squamous cell carcinomas (Moore et al 2004). Patients with locally advanced HNSCC enclose a bad prognostic group with less than 30% of surviving patients five years since finishing treatment, despite the improvements in surgery and new therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%